Economies and Management as A Result of The Fourth Industrial Revolution: An Education Perspective - Jakhongir Shaturaev (Universitas Pendidikan Indonesia (UPI), 2023)
The fourth industrial era (or Industry 4.0) refers to the recent trend of massive data collection, analysis, and communication with intense process automation. Massive studies have been conducted in this field, though with the main focus on technical details, hardware, and software. There remains a considerable gap in the analysis of the potential effects of the Fourth Industrial Revolution on economies and management. According to recent studies, from 45% to 60% of jobs around the globe are at risk of being automated or computerized. Although new jobs such as automation engineers, programmers, data analysts, and others are being created, the economies would get a significant amount of workforce lacking the necessary qualifications. A causal model that shows the effect of increasing automation on economies has been developed and discusses potential implications. The paper suggests that economies and organizations would have to adopt “Algorithmic Management” to remain competitive in the new digital environment. This paper can be a reference, especially from an education perspective.